The effect of block and traditional periodization models on jumping and sprinting dynamics during the simulated basketball games - Pliauga, V.; Lukonaitiene, I.; Bradauskiene, K.; Kliziene, I.; Conte, D.; Stanislovaitiene, J. (Baltic Journal of Sport and Health Sciences, 2018)
Background. The aim of the study was to compare the effect of block and traditional periodization preseason preparation on advanced players` jumping and sprinting dynamics during the simulated basketball games. Methods. Ten college-level males (age (mean ± standard deviation (SD)), 21.5 ± 1.7 years; weight, 83.5 ± 8.9 kg; height, 192.5 ± 5.4 cm) were divided into two teams according to the training model: block periodization (BP) and traditional periodization (TP). Block periodization (BP) consisted of the following blocks: aerobic endurance (AE), power endurance (PE), basketball specific aerobic endurance (BSAE), and power (P). Both groups played a simulated basketball game with each other before and after preseason preparation. Vertical countermovement jump and 20 meters sprint were measured before each simulated game and after each quarter of the game. Results. In BP, the 8 weeks of preseason training resulted in elevated vertical jump and 20 meters sprint dynamics during simulated games (p < .05). Conclusion. We conclude that 8 weeks of block periodization enhanced leg power production and sprint abilities during simulated games and therefore is more effective than traditional periodization model.